Chinese university students sleep patterns amid Covid-19 home quarantine - Deng, Xiang; Wang, Xiaoling; C. Hassan, Norlizah (Human Resource Management Academic Research Society, 2022)
Objective: Investigate the sleep patterns and prevalence of sleep disorders among Chinese university students during the home quarantine of coronavirus disease 2019 (COVID-19), so as to provide the scientific basis for sleep counselling. Methods: Using a random sampling method, 7,364 university students were selected to participate in the survey from April to May 2020. Using PSQI to investigate the sleep status of Chinese university students in home quarantine during the pandemic. Results: (1) The mean PSQI score of those university students was 3.83 ± 2.60, and the mean bedtime was 23:29 ± 1:08, with only 51.87% (3820) of them falling asleep before 23:00; (2) The average sleep efficiency of Chinese university students was 75.76 %± 9.89%%, with 23.51% (1731) of Chinese university students sleep efficiency less than 85% and the incidence of sleep disorders was 8.73% (643); (3) Male students sleep better compared to female students; (4) Senior university students were more likely to have sleep problems compared to junior university students. Conclusion: There were some differences in the sleep patterns of university students between males and females and different grades, with female students having worse sleep patterns compared to male students and senior students having worse sleep patterns than their junior counterparts.